Optimal. Leaf size=23 \[ e^{3+\frac {2 e}{x (-4+4 x)}}+x-\log (x) \]
________________________________________________________________________________________
Rubi [A] time = 1.15, antiderivative size = 25, normalized size of antiderivative = 1.09, number of steps used = 9, number of rules used = 7, integrand size = 70, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.100, Rules used = {1594, 27, 12, 6688, 6742, 43, 6706} \begin {gather*} x+e^{3-\frac {e}{2 (1-x) x}}-\log (x) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 12
Rule 27
Rule 43
Rule 1594
Rule 6688
Rule 6706
Rule 6742
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^{1+\frac {e-6 x+6 x^2}{-2 x+2 x^2}} (1-2 x)-2 x+6 x^2-6 x^3+2 x^4}{x^2 \left (2-4 x+2 x^2\right )} \, dx\\ &=\int \frac {e^{1+\frac {e-6 x+6 x^2}{-2 x+2 x^2}} (1-2 x)-2 x+6 x^2-6 x^3+2 x^4}{2 (-1+x)^2 x^2} \, dx\\ &=\frac {1}{2} \int \frac {e^{1+\frac {e-6 x+6 x^2}{-2 x+2 x^2}} (1-2 x)-2 x+6 x^2-6 x^3+2 x^4}{(-1+x)^2 x^2} \, dx\\ &=\frac {1}{2} \int \frac {e^{4+\frac {e}{2 (-1+x) x}} (1-2 x)+2 (-1+x)^3 x}{(1-x)^2 x^2} \, dx\\ &=\frac {1}{2} \int \left (\frac {2 (-1+x)}{x}-\frac {e^{4+\frac {e}{2 (-1+x) x}} (-1+2 x)}{(-1+x)^2 x^2}\right ) \, dx\\ &=-\left (\frac {1}{2} \int \frac {e^{4+\frac {e}{2 (-1+x) x}} (-1+2 x)}{(-1+x)^2 x^2} \, dx\right )+\int \frac {-1+x}{x} \, dx\\ &=e^{3-\frac {e}{2 (1-x) x}}+\int \left (1-\frac {1}{x}\right ) \, dx\\ &=e^{3-\frac {e}{2 (1-x) x}}+x-\log (x)\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.15, size = 28, normalized size = 1.22 \begin {gather*} e^{3+\frac {e}{2 (-1+x)}-\frac {e}{2 x}}+x-\log (x) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 1.40, size = 37, normalized size = 1.61 \begin {gather*} {\left (x e - e \log \relax (x) + e^{\left (\frac {8 \, x^{2} - 8 \, x + e}{2 \, {\left (x^{2} - x\right )}}\right )}\right )} e^{\left (-1\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.24, size = 48, normalized size = 2.09 \begin {gather*} x + e^{\left (\frac {4 \, x^{2}}{x^{2} - x} - \frac {4 \, x}{x^{2} - x} + \frac {e}{2 \, {\left (x^{2} - x\right )}} - 1\right )} - \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.24, size = 29, normalized size = 1.26
method | result | size |
risch | \(x -\ln \relax (x )+{\mathrm e}^{\frac {{\mathrm e}+6 x^{2}-6 x}{2 x \left (x -1\right )}}\) | \(29\) |
norman | \(\frac {x^{3}+x^{2} {\mathrm e}^{\frac {{\mathrm e}+6 x^{2}-6 x}{2 x^{2}-2 x}}-x -x \,{\mathrm e}^{\frac {{\mathrm e}+6 x^{2}-6 x}{2 x^{2}-2 x}}}{x \left (x -1\right )}-\ln \relax (x )\) | \(77\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.48, size = 25, normalized size = 1.09 \begin {gather*} x + e^{\left (\frac {e}{2 \, {\left (x - 1\right )}} - \frac {e}{2 \, x} + 3\right )} - \log \relax (x) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 8.52, size = 55, normalized size = 2.39 \begin {gather*} x-\ln \relax (x)+{\mathrm {e}}^{\frac {6\,x}{2\,x-2\,x^2}}\,{\mathrm {e}}^{-\frac {6\,x^2}{2\,x-2\,x^2}}\,{\mathrm {e}}^{-\frac {\mathrm {e}}{2\,x-2\,x^2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.28, size = 26, normalized size = 1.13 \begin {gather*} x + e^{\frac {6 x^{2} - 6 x + e}{2 x^{2} - 2 x}} - \log {\relax (x )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________